Force-velocity profiles of dancers and endurance runners during ankle-specific stretch-shortening cycle tasks - Rice, P. E.; Zwetsloot, K. A.; Needle, A. R.; Bruce, A. S.; Guthrie, C. D.; Gillen, L. A.; Nimphius, S. (ISBS Proceedings Archive (Michigan), 2018)
While dance and endurance running drastically differ from one another in an anecdotal context, both modalities of movement necessitate proficient stretch-shortening cycle (SSC) function about the ankle-joint. The purpose of the present study was to compare force-velocity profiles in dancers (n=6) and endurance runners (n=6) during a countermovement hop (CMH) and 30 cm drop hop (DH30) to elucidate differences between groups that would potentially stimulate effective training regimens. Average relative force-time, velocity-time and force-velocity curves were generated for each group`s CMH and DH30. Dancers hopped significantly higher (p = 0.05) than endurance runners in both hopping tasks. Data from this investigation indicate that dancers and runners have distinctive temporal patterns and force production characteristics during ankle-joint SSC tasks with respect to the eccentric and concentric phase. This may be due to the unique SSC characteristics of each group`s corresponding training protocols.